IMPLEMENTATION OF PROFILE MATCING METHOD FOR SELECTION OF THE BEST STUDENT - lasma siagian (Fakultas Keguruan dan Ilmu Pendidikan, Universitas HKBP Nom- mensen, 2020)
Growing awareness of the decision support needs and the desire to get a better information. Higher Education each year holds a large selection of high achieving students, namely students who have good achievements and meet the applicable requirements that must be met. To help determine the winner determination and find the best alternative, high achieving students who are able to provide alternative solutions can use the profile matching method. The use of the Profile Matching method very precise due to this method being able to select some of the best alternatives from aspects of existing criteria. In using this method the weight value for each aspect is required, such as Academic and non-Academic aspects carried out by the Student, after that the rankinged is carried out for all prospective students who excel in the selection a participants, and the results of selection use for decision-making in the determination of outstanding students.